Mathematics  Trigonometric Identities
posted by Anonymous .
Prove:
(tanx)(sinx) / (tanx) + (sinx) = (tanx)  (sinx) / (tanx)(sinx)
What I have so far:
L.S.
= (sinx / cosx) sinx / (sinx / cosx) + sinx
= (sin^2x / cosx) / (sinx + (sinx) (cosx) / cosx)
= (sin^2x / cosx) / (cosx / sinx + sinxcosx)

your equation is not an identity the way you wrote it,
try substituting any angle into the equation, it will not satisfy the equation.
The way you wrote it,
LS reduces to simply 2sinx
use brackets to identify the exact order of operation.